Who Are the "Lazy" Ants? The Function of Inactivity in Social Insects and a Possible Role of Constraint: Inactive Ants Are Corpulent and May Be Young and/or Selfish. (25th July 2017) - Charbonneau, Daniel; Poff, Corey; Nguyen, Hoan; Shin, Min C.; Kierstead, Karen; Dornhaus, Anna
Abstract: Social insect colonies are commonly thought of as highly organized and efficient complex systems, yet high levels of worker inactivity are common. Although consistently inactive workers have been documented across many species, very little is known about the potential function or costs associated with this behavior. Here we ask what distinguishes these "lazy" individuals from their nestmates. We obtained a large set of behavioral and morphological data about individuals, and tested for consistency with the following evolutionary hypotheses: that inactivity results from constraint caused by worker (a) immaturity or (b) senescence; that (c) inactive workers are reproducing; that inactive workers perform a cryptic task such as (d) acting as communication hubs or (e) food stores; and that (f) inactive workers represent the "slow-paced" end of inter-worker variation in "pace-of-life." We show that inactive workers walk more slowly, have small spatial fidelity zones near the nest center, are more corpulent, are isolated in colony interaction networks, have the smallest behavioral repertoires, and are more likely to have oocytes than other workers. These results are consistent with the hypotheses that inactive workers are immature and/or storing food for the colony; they suggest that workers are not inactive as a consequence of senescence, and that they are not acting as communication hubs. The hypotheses listed above are not mutually exclusive, and likely form a "syndrome" of behaviors common to inactive social insect workers. Their simultaneous contribution to inactivity may explain the difficulty in finding a simple answer to this deceptively simple question.